KREDIT MACET BANKALTIM TERMASUK RESIKO USAHA ATAU KORUPSI - Dudin Waluyo Asmoro (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRACTCorruption is an extraordinary crime or crimes remarkable, that could kill and devastated civilization. How many million people become poor because of corruption, how many millions of people do not go to school because of corruption, how many millions of people can not enjoy free medical treatment because of corruption, how many millions of displaced people do not have appropriate housing as a source of income to finance the State and the State budget was corrupted. Corruption indeed deserves to be called an extraordinary crime, crimes against humanity and ready undermined this nation devastated byslowly. Corruption in Indonesia is very widespread and has entered throughout society, not least the banking community. Criminal offense banking rife lately, still shows a weakness in the banking system so that the gap can be utilized by unscrupulous bankers who have evil intentions, which may also relate to the crime one other criminal offense of corruption.